A New Approach in the Study of Oscillation Criteria of Even-Order Neutral Differential Equations - Osama Moaaz; Jan Awrejcewicz; Omar Bazighifan (Mathematics, 2020)
Based on the comparison with first-order delay equations, we establish a new oscillation criterion for a class of even-order neutral differential equations. Our new criterion improves a number of existing ones. An illustrative example is provided.